Interview: Virus-free induction of induced pluripotent stem cells. (May 2009) - Nagy, Andras
Dr Nagy is currently a Senior Scientist at the Samuel Lunenfeld Research Institute, Mount Sinai Hospital, Professor in the Department of Molecular Genetics at the University of Toronto and Investigator at the McEwen Centre for Regenerative Medicine. He also holds a Tier I Canada Research Chair in Stem Cells and Regeneration. His research focuses on several areas of interest, which include: functional studies of genes belonging to families with known roles in vessel formation; development of sophisticated genetic manipulation tools in the mouse model; applying genetics to cancer research; derivation, differentiation and genetic modification of both mouse and human embryonic stem cells; and reprogramming of somatic cells to pluripotent stem cells. Dr Nagy''s research is currently funded by the National Cancer Institute of Canada, Genome Canada, Stem Cell Network, NSERC and the NIH.